33‐2: Flexible OLED Panels with Pixilated Graphene Anode. Issue 1 (30th May 2018) - Shin, Jin-Wook; Cho, Hyunsu; Kwon, Byoung-Hwa; Han, Jun-Han; Lee, Kang Me; Yang, Jong-Heon; Byun, Chun-Won; Lee, Jeong-Ik; Moon, Jaehyun; Cho, Nam Sung
Abstract : Due to the feeble nature of graphene and poor adhesion to its support, it was difficult to pattern graphene film into accurate dimension over a large area. Using a display compatible patterning process, we successfully pixelated graphene film in an array on a flexible substrate and used that array for flexible OLED anodes. We discuss and propose processing strategies which enable integration of individual components into a flexible OLED panel. Finally, we demonstrate a fully operational flexible OLED panel (40 mm × 40mm) which has pixelated graphene film as transparent electrode. Our integration scheme suggests a display technology compatible approach for using graphene in flexible AM ‐ OLED display applications.